2021
DOI: 10.3390/inventions6040069
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Performance Enhancement of a Photovoltaic Module Using a Combination of Phase Change Material and Aluminum Fins—Exergy, Energy and Economic (3E) Analysis

Abstract: The electrical performance of a photovoltaic (PV) module is hugely affected by its temperature. This study proposed a passive cooling mechanism for the cooling of a PV panel. The proposed cooling system is made up of a combination of aluminum fins and paraffin wax integrated at the PV panel’s rear side. The average temperature for the cooled panel for the entire period of the experiment is 36.62 °C against 48.75 °C for the referenced PV module. This represents an average reduction of 12.13 °C for the cooled pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…The above effect may be important, as summer in central Europe has become hotter over the past decade. It should be noted that there are a lot of technologies that are available in energy markets to increase the efficiency of a PV panel, for instance [43][44][45][46]. These technologies are mainly based on cooling PV panels through the use of heat sinks or water cooling.…”
Section: Methodsmentioning
confidence: 99%
“…The above effect may be important, as summer in central Europe has become hotter over the past decade. It should be noted that there are a lot of technologies that are available in energy markets to increase the efficiency of a PV panel, for instance [43][44][45][46]. These technologies are mainly based on cooling PV panels through the use of heat sinks or water cooling.…”
Section: Methodsmentioning
confidence: 99%
“…For example, when O t = 10, X t+1 = 15 and β t = 0.3, the parameters are updated, as expressed in Equation (10).…”
Section: Application Of On-demand Dsmm To Solar Power Generationmentioning
confidence: 99%
“…However, they did not mention the balance of solar power generation between supply and demand. Agyekum et al (2021) [10] conducted an experiment on the performance enhancement of a solar PV from exergy, energy, and economy. They improved the performance by the cooling of a PV panel though they did not mention the balance of solar power generation between supply and demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agyekum et al [13] found about a 12% improvement in energy efficiency and a 30% increase in power generation compared to the uncooled panels by using a cotton wick to cool the PV panels. They also discovered that the electricity efficiency of the PV panels can be improved by 6.8% and 5.85%, respectively, when using a heat sink (made up of aluminum fins and an ultrasonic humidifier) and a cooling system (made up of aluminum fins and paraffin wax) [14,15]. Similarly, PraveenKumar et al [16] experimented with the aluminum sheets mounted PV panel module and found about a 4% increase in electricity efficiency and a 9.4% improvement in electricity generation, compared to conventional panels.…”
Section: Introductionmentioning
confidence: 99%